1997
DOI: 10.1063/1.118849
|View full text |Cite
|
Sign up to set email alerts
|

Low-dispersion thin-film microstrip lines with cyclotene (benzocyclobutene) as dielectric medium

Abstract: We report on thin-film microstrip lines (TFMSLs) fabricated on low-resistivity Si with polymerized cyclotene as the dielectric between signal and ground conductor, all on top of the wafer. Electro-optic high-frequency characterization of the TFMSLs reveals negligible modal dispersion up to the highest frequencies of 1.0 THz. In spite of the high substrate conductivity, the attenuation is low (⩽1 dB/mm at 100 GHz). Over the full frequency range, it is dominated by conductor losses and not by absorption in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…10(d). Frequency-domain propagation parameters (not shown here) of the wire have been retrieved from the time-domain data by a procedure described in [55]. Using these freely-positionable PC probetips the frequency-dependent attenuation and dispersion behaviour of Sommerfeld wires was measured in qualitative and quantitative agreement with numerical field simulations [64].…”
Section: Application Examples: Thz Waveguide Probe-tip and Antenna Dmentioning
confidence: 71%
See 2 more Smart Citations
“…10(d). Frequency-domain propagation parameters (not shown here) of the wire have been retrieved from the time-domain data by a procedure described in [55]. Using these freely-positionable PC probetips the frequency-dependent attenuation and dispersion behaviour of Sommerfeld wires was measured in qualitative and quantitative agreement with numerical field simulations [64].…”
Section: Application Examples: Thz Waveguide Probe-tip and Antenna Dmentioning
confidence: 71%
“…7 have been used for the fabrication of integrated PC switches on host substrates. The first two concepts differ by the order of the process steps of LT-GaAs transfer and metal electrode (planar waveguide) structuring on the HS [53,55]. In a third alternative, the electrode structures are defined on the LT-GaAs chip before it is transferred to the HS.…”
Section: Epitaxial Lift-off Fabrication Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cherenkov radiation loss was eliminated by the use of silicon-on-insulator materials with a microstrip geometry [32] and thin-film microstrip lines [33], but the total observed loss owing to the dielectric and the metal was still approximately the same as that for the coplanar transmission line. A variety of transmission line structures have been designed to reduce the permittivity mismatch responsible for the Cherenkov radiation [34]- [37].…”
Section: A Methods To Eliminate Cherenkov Radiation From Transmissiomentioning
confidence: 94%
“…Though a silica-based membrane was presented in the previous work [8], it is not simple in fabrication and not very robust mechanically. On the other hand, in 1997, a low loss and small dispersion propagation was reported using the MSLs with 10 μm-thickness dielectric layer based on low permittivity polymer materials [9]. It was also demonstrated that the MSLs can be used as a sensitive label-free detector of DNA molecules, by using a resonator structure in the MSL, though the spectral range of the devices was still in sub-THz range [10].…”
Section: Introductionmentioning
confidence: 98%